A phase II study of bortezomib in patients with relapsed or refractory aggressive adult T‐cell leukemia/lymphoma. Issue 9 (September 2015) - Ishitsuka, Kenji; Utsunomiya, Atae; Katsuya, Hiroo; Takeuchi, Shogo; Takatsuka, Yoshifusa; Hidaka, Michihiro; Sakai, Tatsunori; Yoshimitsu, Makoto; Ishida, Takashi; Tamura, Kazuo
<x xml:space="preserve">Abstract</x> Adult T‐cell leukemia/lymphoma (ATL) is a malignancy of peripheral T‐lymphocytes with a poor prognosis. This multicenter, two‐stage, single‐arm, phase II study assessed the efficacy and safety of bortezomib in patients with relapsed/refractory ATL who received at least one regimen of chemotherapy. The primary endpoint was the best overall response rate (ORR), and secondary endpoints included safety, the best response by lesions, and progression‐free survival (PFS). Fifteen patients were enrolled in the first stage of this study. One partial remission (PR) and five stable disease (SD) were observed as the best overall responses, and ORR was 6.7% (95% confidence interval (C.I.) 0.17‐31.95%). Responses according to disease sites were one complete remission (CR) in peripheral blood, two PR in measurable targeted lesions, and two PR in skin lesions. Progression‐free survival (PFS) was 38 (95% CI; 18–106) days. All patients developed ≥1 adverse events (AEs), and 80% of patients had ≥1 grade 3/4 AEs; however, no new safety findings were obtained. Although these results fulfilled the planned settings to proceed to the second stage, the coordinating committee decided to terminate this study because single agent activity did not appear to be very promising for this cohort of patients.